Dinâmicas do reconhecimento: a (re) constituição do habitus do professor universitário - Atayde, Vanessa Martins de (2013)
This study is the result of a field research theme of "social dynamics of recognition and the establishment of the university teacher habitus", made from semi-structured interviews that focused on family and school career / academic. The selected group of teachers was considered a department of excellence in science, from a public university in the state of São Paulo. Had we assume the formation of a habitus that is peculiar to these professionals and that related to the social construction of a professional identity and associated personnel rules and practices of academic-scientific. The objective was to analyze the existence of the relationship between the dynamics of recognition in the scientific field and the establishment of lasting provisions peculiar to their agents, which have shown to be associated with an ideal of performativity and success. In this perspective, from the use of qualitative research method and emphasis on discourse analysis as relevant social practice, we analyzed the relationships between values, choices and needs that guide individuals' sense of investment in scientific field; investment in their rules and their "game" peculiar.